2019
DOI: 10.1200/jgo.19.00209
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Randomized Trial to Facilitate Breast Cancer Early Diagnosis in a Rural District of Rwanda

Abstract: PURPOSEFeasible and effective strategies are needed to facilitate earlier diagnosis of breast cancer in low-income countries. The goal of this study was to examine the impact of health worker breast health training on health care utilization, patient diagnoses, and cancer stage in a rural Rwandan district.METHODSWe conducted a cluster randomized trial of a training intervention at 12 of the 19 health centers (HCs) in Burera District, Rwanda, in 2 phases. We evaluated the trainings’ impact on the volume of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 9 publications
0
32
0
Order By: Relevance
“…Using a cluster randomized controlled trial design, Pace et al reported on the efficacy of a training program for health workers in Rwanda targeting the early diagnosis of breast cancer. Compared to the control group, health centers receiving the intervention experienced a statistically significant increase in breast cancer referrals (1484 visits [increase of 7.9 visits/month] vs 308 visits; P = .007) and an increase in incidence of early stage disease (3.3/100 000 vs 0.7/100 000 person‐years; P = .048) in intervention areas 35 . Other studies have also demonstrated the efficacy of training community health workers in the early detection and referral of breast and cervical cancer 35–41 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Using a cluster randomized controlled trial design, Pace et al reported on the efficacy of a training program for health workers in Rwanda targeting the early diagnosis of breast cancer. Compared to the control group, health centers receiving the intervention experienced a statistically significant increase in breast cancer referrals (1484 visits [increase of 7.9 visits/month] vs 308 visits; P = .007) and an increase in incidence of early stage disease (3.3/100 000 vs 0.7/100 000 person‐years; P = .048) in intervention areas 35 . Other studies have also demonstrated the efficacy of training community health workers in the early detection and referral of breast and cervical cancer 35–41 .…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the control group, health centers receiving the intervention experienced a statistically significant increase in breast cancer referrals (1484 visits [increase of 7.9 visits/month] vs 308 visits; P = .007) and an increase in incidence of early stage disease (3.3/100 000 vs 0.7/100 000 person‐years; P = .048) in intervention areas 35 . Other studies have also demonstrated the efficacy of training community health workers in the early detection and referral of breast and cervical cancer 35–41 . Whether such interventions in the adult cancer space can translate effectively to improvments in the early detection of childhood cancers in LMICs is a subject for future research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the prevalence of cervical cancer in Rwanda, and the complexity of the current cervical cancer treatment pathway that requires multi-institutional referrals, building strategies to improve community knowledge about cervical cancer, screen women for cervical cancer, connect them to care and help them navigate the health system will be imperative. At BCCOE, a training program was initiated in Burera District in 2015 to facilitate earlier diagnosis of breast cancer and has been shown to improve community health workers’ and health center nurses’ knowledge and skills in evaluating and managing breast concerns, increase the number of women visiting a health center for a breast concern, and increase the incidence of early stage breast cancer [ 29 30 ]. At the Ministry of Health’s request, this model was expanded to additional districts and to include cervical cancer screening in 2018.…”
Section: Discussionmentioning
confidence: 99%